If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(z + -4) + 6z + -1 = 0 Reorder the terms: 6(-4 + z) + 6z + -1 = 0 (-4 * 6 + z * 6) + 6z + -1 = 0 (-24 + 6z) + 6z + -1 = 0 Reorder the terms: -24 + -1 + 6z + 6z = 0 Combine like terms: -24 + -1 = -25 -25 + 6z + 6z = 0 Combine like terms: 6z + 6z = 12z -25 + 12z = 0 Solving -25 + 12z = 0 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '25' to each side of the equation. -25 + 25 + 12z = 0 + 25 Combine like terms: -25 + 25 = 0 0 + 12z = 0 + 25 12z = 0 + 25 Combine like terms: 0 + 25 = 25 12z = 25 Divide each side by '12'. z = 2.083333333 Simplifying z = 2.083333333
| 27x^3-12x=0 | | 12x+11=60 | | 4x+5=-6x-15 | | 9+1.88888888889-13=4 | | 4(3z+4)=2(6m+8) | | 9+5x=7x+12-2x | | 16x^2+121=0 | | -10x+9=50 | | -3/4=h/22 | | -4(3-t)=8(t+2) | | 0.05x=2.857x+0.06 | | 3/8(m+16)=9 | | 20x=2.857x+0.06 | | -20x=2.857x+0.06 | | 3.2+.17w=5.75 | | -14n+14n=-10 | | .70(x+100)+.10x=86 | | 3/8m+3=9 | | 2(2+.5l)=40 | | 3x/8+3/4=9 | | x+3-x-3=6 | | x+3-x-3= | | 6+3b=2 | | C(c+1)=1.10 | | 8=2g-12 | | 9=g-13 | | 15=g+9 | | 8f=f-28 | | 5f=f-24 | | 4+6(w-2)+w= | | 7(x)+9+3(x)+4=143 | | 2[w-(4w+9)+3]=2(w+6) |